Gastric adenocarcinoma with enteroblastic differentiation [case report] - Ferenczi Ádám (PATHOBIOLOGY, 2025)
Introduction: Gastric adenocarcinoma with enteroblastic differentiation (GAED) is a rare entity with worse prognosis compared to conventional gastric adenocarcinomas. Its histological characteristics are fetal gut-like architecture and tumor cells with cytoplasmic clearing, as well as positive immunohistochemical reaction to at least one of the enteroblastic markers. Hereby, we present a case of GAED with neuroendocrine marker positivity, with whole exome sequencing (WES), and an updated literature review.Case presentation: A 68-year-old woman presented with abdominal pain. Gastric wall thickening raised suspicion of gastric cancer, thus gastroscopy was performed, and biopsy samples were taken, which confirmed malignancy. Neoadjuvant systemic chemotherapy was initiated, and total gastrectomy was performed. Microscopically, pleomorphic polygonal cells were visible with clear cytoplasm and high grade cellular atypia. Alcian blue and PAS stains demonstrated positivity for acidic and neutral mucins. P53 IHC was negative, indicative of null-phenotype, while Syntaxin-1 and Chromogranin showed focal positivity. SALL4 and Glypican 3 were positive, however, AFP displayed only minimal, uncertain positivity. The Ki67 labeling index was 70%. Due to the morphological and immunohistochemical characteristics, the tumor was concluded as GAED with neuroendocrine marker positivity. WES was carried out revealing 4 pathogenic, including TP53, KLHL7, RAPSN, and ACTA1, and 3 likely pathogenic mutations, encompassing PNKP, HNF1A, and ADNP.Discussion: GAED is a rare subtype of gastric adenocarcinomas, representing 0.3-5.4% of all cases and has an unclarified etiology. Our WES results identified new pathogenic and likely pathogenic mutations. From a differential diagnostic point of view, hepatoid adenocarcinoma, and the possibility of metastatic origin has to be excluded.